The rescue of Lusia by Albion: Representations of Portugal in british women’s peninsular war poetry - Guimarães, Paula Alexandra (2016)
For long considered as exclusive male preserves, war and military conflict have affected and interested a background of a singular poem by Charlotte E. Tonna, The Convent Bell (1819, 1845), about an ill-fated romance between an Irish soldier and a Portuguese nun during the first years of the campaign. Dedicated to Wellington, this Romantic plot “endowed with a strong political and military subtext” (Saglia, 2000: 226) presents an official, male-sanctioned discourse of the conflict, being a (re)presentation of the submissive number of female authors in the nineteenth century. The Peninsular War (1808-14), in particular, is the foreign female figure as the rescued/dominated territory. But it, furthermore, closely resembles other poetic writings by well-known Romantic female authors, such as those of Felicia Hemans on the Peninsular Wars (England and Spain of 1808 and Domestic Affections of 1812), who herself had personal, political and artistic interests in Iberian subjects and the representation of women in European history.